The student’s self-assessment in the improved processes of the university degree courses - Refrigeri, Luca; Palladino, Florindo (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2019)
As part of the self-assessment activities of Primary Education course at University of Molise, in order to acquire further data beyond those usually available and reduce the degree of self-reference, they were associated with students in the last year of the study path and graduates (teachers), through the administration of a questionnaire aimed at detecting the degree of skills acquired in the various disciplinary fields, identified in the SUA of the CdS as learning objectives. The quantitative analysis of the surveyed data has identified to identify, for each disciplinary area of the course, the level of acquisition of competences, as perceived by undergraduates and teachers; has allowed, determined, to undertake specific improvement actions both in the areas found critical and in those where the interviewees perceive themselves on average more competent. In the latter case, attention was paid to learning objectives that may no longer be useful to the actual needs of the course of study.The research experience carried out, involved at the same time, a contribution to the improvement of the specific course of study but also a useful practice for those who consider the self-evaluation process a mere administrative and bureaucratic fulfillment.